2014
DOI: 10.1371/journal.pone.0088311
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Dendritic Cells Arising from Progenitors Endogenous to Murine Spleen

Abstract: Heterogeneity amongst dendritic cell (DC) subsets leads to a spectrum of immune response capacity against pathogens. Several DC subsets in spleen have been described which differ in terms of phenotype and function. We have previously reported a distinct population of CD11cloCD11bhiMHC-II−CD8− dendritic-like “L-DC” in murine spleen, which can also be generated in splenic stromal longterm cultures. Here, the ontogeny of L-DC development in perinatal mice has been compared with other known splenic DC subsets. Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
(72 reference statements)
3
31
0
Order By: Relevance
“…Antibody staining followed by flow cytometry was performed to analyze cell surface marker expression as described previously ( 32 ). Non-specific antibody binding via Fc receptors was blocked by incubating cells (≤ 10 6 ) with anti-CD16/32 (FcBlock) (Biolegend: San Diego, CA, USA) at 5 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody staining followed by flow cytometry was performed to analyze cell surface marker expression as described previously ( 32 ). Non-specific antibody binding via Fc receptors was blocked by incubating cells (≤ 10 6 ) with anti-CD16/32 (FcBlock) (Biolegend: San Diego, CA, USA) at 5 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Novel dendritic-like cells termed L-DC, were recently discovered in murine and human spleen on the basis of their resemblance with dendritic-like cells produced in vitro in splenic long-term cultures (LTC-DC) ( 28 30 ), or in co-cultures of bone marrow precursors over selected splenic stroma ( 31 , 32 ). L-DC have a distinct CD11b hi CD11c lo MHCII − CD8 − phenotype and dendritic-like appearance ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has become clear that L-DC progenitors in vivo reflect HSC endogenous to spleen, and that the process of L-DC development reflects extramedullary hematopoiesis. L-DC progenitors first appear in murine spleen at E18.5, while progenitors of cDC appear after 4 days (Petvises and O'Neill, 2014a). This raises the possibility that hematopoietic progenitors in spleen are laid down during ontogeny, and that hematopoiesis in spleen giving rise to differentiation of dendritic-like L-DC occurs as an active process, independent of inflammatory signalling.…”
Section: Evidence That Splenic Stroma Supports Hematopoiesismentioning
confidence: 99%
“…Previous studies have demonstrated the ability of the murine 5G3 splenic stroma to support myelopoiesis from hematopoietic stem/progenitor cells present in both murine bone marrow and spleen. 12,14,15,30,31 Cell growth was monitored, and non-adherent cells were collected and flow cytometrically assessed at 7-day intervals. Live cells were gated, and HLA-DR versus hCD11c staining was used to delineate any dendritic-like cells produced in the cocultures.…”
Section: The Human Spleen Contains Cells Resembling Murine L-dcsmentioning
confidence: 99%